Effectiveness of Tiger Method in Learning Mathematics of IX Standard Students - S. , Muthulakshmi; H. , Deepa (International Journal of Psychosocial Rehabilitation, 2020)
The present study visions to find out the effectiveness of the TIGER method in learning mathematics among IX standard students. This is an experimental study with a pretest-posttest equivalent group design. A sample of 60 IX standard students was chosen for the study. The investigators applied self-developed Mathematical Achievement test to assess the achievement. Data were analyzed using ANCOVA and a t-test to determine the performance comparing the mean scores. The findings implied that the experimental group performed better than the control group in the posttest. It was found that the TIGER method had the power to make the students perform better than their counterparts taught through the traditional method.